PERSEBARAN DAN TIPE HABITAT BEKANTAN (Nasalis larvatus) DI KABUPATEN BARITO KUALA, KALIMANTAN SELATAN - Mochamad Arief Soendjoto; Muhammad Akhidayat; Haitami .; Indra Kusumajaya (Media Konservasi, 2001)
Although proboscis monkey (Nasalis larvatus) is one of protected animals and is stated as the identity fauna of South Kalimantan Province, its distribution in this province is poorly documented. The main objectives of the preliminary reserach were to understand distribution and habitat type of proboscis monkey inhabiting Barito Kuala District. The results show that: 1) population of proboscis monkeys is a minimum 0f 289 individuals and 22,14% of this population inhabits the protected areas, 2) habitat types are not only mangrove forest and riparian forest, there are factors affecting positively and negatively on conservation of probosics monkey. Some negative factors are conversion of galam forest to be rice yeld, negative attitude of people on proboscis monkey sustainable, lack of people knowledge on this animals status and opinion that this animal is a pest.